Pengolahan Limbah Cair Budidaya Ikan Lele Menggunakan Metode Anaerob dengan Media Bambu - Sagala, Johannes Kevin Adam Jordan; Sulastri, Aini; Desmaiani, Herda (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
The catfish farming industry is an industry that uses a lot of water for its production process, so the amount of waste produced is quite large. Waste from fish farming activities generally results from the accumulation of leftover feed used for catfish consumption and the excretion results of the fish being kept. Waste produced from fish farming activities contains organic material in the form of particles. The aim of this research is to analyze the quality of waste water produced in catfish cultivation in terms of the water quality parameters in freshwater fish cultivation SNI 7550:2009, and the efficiency produced in processing liquid waste using the anaerobic method with bamboo media. This research uses the Anaerobic Processing method with bamboo media. Water samples are taken using the grab sampling method. The area studied is the residential scale catfish farming industry. The quality of wastewater discharged from catfish farming, most parameters such as dissolved oxygen (DO), Cadmium (Cd), Lead (Pb), ammonia (NH3), and nitrite (NO2-) do not meet the quality standards specified in SNI 7550: 2009. The anaerobic method significantly succeeded in reducing the concentration of ammonia (NHâ‚ƒ) with an efficiency of 83% and nitrite (NOâ‚‚â») with an efficiency of 89%, showing efficiency in reducing nitrogen compounds that are harmful to aquatic ecosystems